PENGGUNAAN MODEL PEMECAHAN MASALAH UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR ANALISIS PESERTA DIDIK PADA MATERI GRAVITASI NEWTON - Sabaruddin Sabaruddin (Lantanida Journal, 2019)
Mathematical analytics Important, analytical skills When students are able to understand analysis in physics learning, students will be able to answer questions with questions that are different from the examples given by the teacher. The aim of studying the increased thinking of participants in cognitive taxonomy analysis in Newton's law materials was approved using problem solving learning models. Hypothesis testing is done by comparing the average value of the ability of the initial test (pre-test) and the average ability of the final test (post-test) of students. The process of testing the hypothesis will test the normality and homogeneity test as a requirement to use parametric statistics, namely by using the t-test. Based on the results of the study obtained a value of tcount (8.25) and ttable value at dk = 42 with a 95% confidence level obtained at 2.02. This shows that tcount> t table. So can it be concluded that the expansion of students' thinking analysis ideas on cognitive taxonomy in the legal material used uses problem solving learning models.